Management of Urban Greenery System in Vietnam in the Era of Industry 4.0 - Pham Anh, Tuan (International Journal of Sustainable Construction Engineering and Technology, 2021)
Application of computer software and exploitation database systems bring great benefits and integrate many features in different fields of science and life for urban management including urban greenery management in cities. In Vietnam, they have been being more concerned due to the Vietnamese Government policies in development of e-Government and smart cities. This paper firstly focuses on discussion about the reality of urban greenery management in Vietnam to reveal the problems in management as well as opportunities of this field in application new technology in cities, such as artificial intelligent, information technology, internet of things, ... Secondly, it reviews the current application of science and technology in urban greenery management in the world as well as cities in Vietnam to evaluate the effectiveness, understand a broader context and eventually draw lessons, which can be learned for this field in Vietnamese circumstance. Finally, it discusses the potential to apply the management software and suggests some suitable solutions for the smart urban greenery management, that can provide effective tools and become components to develop and organize smart cities in Vietnam in the era of Industry 4.0.